A Risk-Based Digital Governance Model for Ensuring Programme Assurance in Complex Infrastructure Delivery - Ebimor Yinka Gbabo; Odira Kingsley Okenwa; Possible Emeka Chima (International Journal of Scientific Research in Civil Engineering, 2023)
The growing complexity of infrastructure delivery programmes has heightened the demand for more adaptive, transparent, and risk-sensitive governance mechanisms. Traditional programme assurance approaches—often linear, periodic, and manually driven—struggle to keep pace with dynamic delivery environments characterised by interdependencies, regulatory volatility, and stakeholder pressures. This paper presents a structured, risk-based digital governance model aimed at addressing these challenges by embedding real-time risk logic and digital integration into governance architecture. The model comprises key components including dynamic data flows, decision gateways, risk-tier classifications, and multi-level governance roles across strategic, tactical, and operational layers. It supports continuous assurance through mechanisms such as live dashboards, automated risk registers, and digital twins, enabling early detection, prioritisation, and response to emerging threats. The paper outlines the conceptual foundations, framework components, implementation considerations, and implications for both theory and practice. It concludes by highlighting future research directions focused on effectiveness metrics and cross-sectoral adaptation. The proposed model contributes to the modernisation of programme assurance by aligning digital transformation with risk governance imperatives in complex infrastructure systems.